This Child Will be Great memoir of a remarkable life by Africa?s first woman president - Johnson Sirleaf, Ellen Johnson (New York Harper, 2009)
In January 2006, after the Republic of Liberia had been racked by fourteen years of brutal civil conflict, Ellen Johnson Sirleaf?Africa's "Iron Lady"?was sworn in as president, an event that marked a tremendous turning point in the history of the West African nation. In this stirring memoir, Sirleaf shares the story of her rise to power, including her early childhood; her experiences with abuse, imprisonment, and exile; and her fight for democracy and social justice. She reveals her determination to succeed in multiple worlds, from her studies in the United States to her work as an international bank executive, to campaigning in some of Liberia's most desperate and war-torn villages and neighborhoods. It is the tale of an outspoken political and social reformer who fought the oppression of dictators and championed change. By telling her story, Sirleaf encourages women everywhere to pursue leadership roles at the highest levels of power, and gives us all hope that we can change the world.
Includes bibliographical references and index
Keywords: Johnson-Sirleaf, Ellen, 1938- Presidents-Liberia-Biography. Women presidents-Liberia-Biography. Liberia-Politics and government -1980- Liberia-Biography.